Comparison of IDRS and ADA Diabetes Risk Assessment Tools Reveals Different Rsk Score in Same Population: A Cross-Sectional Analysis in a Tertiary Care Hospital - Akter, N.; Qureshi, N.K. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: To identify individuals at high risk of developing type2 diabetes (T2DM), use of a validated risk-assessment tool is currently recommended. Nevertheless, recent studies have shown that risk scores that are developed in the same country can lead to different results of an individual. The Objective of study was to reveal whether two different risk-assessment tools predict similar or dissimilar high-risk score in same population.Method: This cross-sectional analytical study was carried upon 336 non-diabetic adults visiting the outpatient department (OPD) of Medicine, MARKS Medical College & Hospital, Bangladesh from October 2018 to March 2019. Woman having previous history of Gestational Diabetes Mellitus (GDM) were also included. Both the Indian Diabetes risk Score (IDRS) and the American Diabetes (ADA) Risk Score questionnaire were used to collect the data on demographic and clinical characteristics, different risk factors of an individual subject, and to calculate predicted risk score for developing T2DM.Results: Among 336 subjects, 53.6% were female. The mean (±SD) age of the study subjects was 38.25±1.12 years. The average IDRS predicted risk score of developing T2DM was more in female subjects than male [p